Выборы как общественно-историческая ситуация: теоретические модели избирательного процесса - Гавриленко, И.; Литвин, А. (Социология: теория, методы, маркетинг, 2000)
The authors regard election as a process of interpersonal social interaction with the purpose of social transformations corresponding the chosen prospective (historical) orientations. Being a socio-historical situation, election is aimed at a re-distribution of power and formation of prerequisites for further evolution of the society. In the democratic society an election adequate to its inner nature constitutes a form of presenting and solving actual social conflicts with political means and, at the same time, a means of struggle of cultural patterns of the future and corresponding alternative projects of its attainment.